Visible-light enhanced photocatalytic performance by lowering the bandgap of reusable TiO2/chitin and ZnO/chitin nanocomposites for trimethoprim degradation - Jonás José Perez Bravo; María Emilia Villanueva; Gabriel Ibrahin Tovar; Nora Judit François; Guillermo Javier Copello (eXPRESS Polymer Letters)
For a nanocomposite, the interaction among nanoparticles (NPs) and the polymeric matrix acting as support has a determinant role in the performance of the material in its intended application. Two UV-sensitive NPs (TiO2 and ZnO) were chosen in order to study the effect of their interaction with chitin in the photocatalytic degradation of trimethoprim, which is an emerging pollutant. Chitin-NPs composites were characterized by structural, thermal, optical, and photoelectrochemical techniques. NPs immobilization into the chitin matrix showed to affect both NPs in the same manner by influencing their photocurrent generation and decreasing the bandgap, which allowed taking advantage of the Visible-light spectrum. Trimethoprim degradation rates under simulated sunlight and chitin chemical stability upon reusability were evaluated. Both composites can be used over a wide range of pH, but the alkaline medium produced a decrease in the chitin:ZnO degradation efficiency. The chemical structure of chitin was not affected by the photocatalysis reaction, even after several cycles. As it was observed for the nude NPs, the chitin:TiO2 composite trimethoprim degradation efficiency was higher than the chitin:ZnO nanocomposite. Chitin matrix allowed an easy recovery of the NPs from the treatment medium and recycling of the material without loss of photocatalytic efficiency.